2023
DOI: 10.1126/sciadv.add7474
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a polymer resistant to bacterial biofilm, swarming, and encrustation

Abstract: Innovative approaches to prevent catheter-associated urinary tract infections (CAUTIs) are urgently required. Here, we describe the discovery of an acrylate copolymer capable of resisting single- and multispecies bacterial biofilm formation, swarming, encrustation, and host protein deposition, which are major challenges associated with preventing CAUTIs. After screening ~400 acrylate polymers, poly( tert -butyl cyclohexyl acrylate) was selected for its biofilm- and encrustation-resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…As the most dominant strain causing bacterial infection strain isolated from US encrustation and blockages, Proteus mirabilis (P. mirabilis) has been found to secrete large amounts of urease during proliferation. [12] This is problematic because urease has a high selectivity to the urea linkage of urinary urea, which can catalyze the hydrolysis of urinary urea to ammonia and increase the urine pH, accelerating the precipitation of Ca 2+ and Mg 2+ crystals and ultimately resulting in encrustation and blockage of the flow channels of stents in a short time. [12,23] Here, we hypothesized that this enzyme activity could act as a biological signal to trigger the selective cleavage of urea linkages in the SA-PU/PVP coating.…”
Section: Urease-responsive On-demand Release Of the Antibiotic Sa Fro...mentioning
confidence: 99%
See 2 more Smart Citations
“…As the most dominant strain causing bacterial infection strain isolated from US encrustation and blockages, Proteus mirabilis (P. mirabilis) has been found to secrete large amounts of urease during proliferation. [12] This is problematic because urease has a high selectivity to the urea linkage of urinary urea, which can catalyze the hydrolysis of urinary urea to ammonia and increase the urine pH, accelerating the precipitation of Ca 2+ and Mg 2+ crystals and ultimately resulting in encrustation and blockage of the flow channels of stents in a short time. [12,23] Here, we hypothesized that this enzyme activity could act as a biological signal to trigger the selective cleavage of urea linkages in the SA-PU/PVP coating.…”
Section: Urease-responsive On-demand Release Of the Antibiotic Sa Fro...mentioning
confidence: 99%
“…[11] Despite this approach being efficient, an increasing number of studies have revealed that the prophylactic application of this strategy can also favor the development of antibacterial resistance because of the uncontrolled and imprecise release profile of incorporated antibiotics. [12] Therefore, "on-demand" release of antibiotics from the antifouling coating triggered by the stimuli (e.g., pH, temperature, and enzymes) in the microenvironment of biofilms is considered as a smart approach to achieve precise antibiotic delivery for reducing the incidence of UTIs and encrustation. [13] In clinical studies, Proteus mirabilis (P. mirabilis) was the most prevalent bacteria in US surface biofilms, which secretes a significant amount of urease that can further promote the deposition of urate crystals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 5,6 ] Successful examples of such materials include poly(ethylene glycol) brushes, [ 7 ] zwitterionic polymers, [ 8 ] liquid‐infused surfaces, [ 9 ] and amphiphilic copolymers (AP). [ 10–15 ] Here, we focus on AP for their capability in mitigating bacterial attachment and biofilm formation at both solid–liquid interfaces and solid–liquid–gas triple interfaces, the latter of which has received far less attention despite their implication in nosocomial material‐associated infections. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] Successful examples of such materials include poly(ethylene glycol) brushes, [7] zwitterionic polymers, [8] liquid-infused surfaces, [9] and amphiphilic copolymers (AP). [10][11][12][13][14][15] Here, we focus on AP for their capability in mitigating bacterial attachment and biofilm formation at both solid-liquid interfaces and solid-liquid-gas triple interfaces, the latter of which has received far less attention despite their implication in nosocomial material-associated infections. [12] While the antibiofouling performance of most polymer coatings has been attributed to hydrophilicity, i.e., the increased enthalpic barrier for foulant adhesion, the fundamental mechanism for AP's fouling resistance is not well understood.…”
Section: Introductionmentioning
confidence: 99%